Pengaruh Game-Based Learning Berbantu Wordwall terhadap Hasil Belajar Siswa - Melan Nurjiah; Jean Elikal Marna (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This research is motivated by the low student learning outcomes in Economics subjects, which are caused by the use of conventional learning models that do not involve students actively. In an effort to overcome this problem, the Game-Based Learning (GBL) learning model, assisted by Wordwall media, is applied to create an interactive and fun learning atmosphere. This research is included in the type of quasi-experimental design with a pretest-posttest control group. The study population was all students of the Phase F XI class, and the sample was selected using a purposive sampling technique. The data collection techniques used were documentation and result tests. The results showed a significant increase in student learning outcomes after applying the GBL model assisted by Wordwall, compared to the conventional learning model. This was proven through statistical tests with significance results <0.05. These findings contribute to the development of innovative learning models in the discipline of economic education. Thus, the use of the Game-Based Learning (GBL) model assisted by Wordwall is proven effective in improving students' learning outcomes, especially in the aspects of concept understanding and analysis skills. This model is important to be applied as an alternative learning strategy that encourages students' active participation and increases their learning motivation.